2017
DOI: 10.3389/fnbeh.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dopamine Transporter Inhibitor CE-123 Improves Cognitive Flexibility and Maintains Impulsivity in Healthy Male Rats

Abstract: Reduced cognitive abilities are often characterized by an impairment of flexibility, i.e., the ability to switch from learned rules or categories that were important in certain contexts to different new modalities that rule the task. Drugs targeting the dopamine transporter (DAT) are widely used for their potential to enhance cognitive abilities. However, commercially available drugs are of limited specificity for DAT, blocking also noradrenaline and serotonine transporters, that can lead to unwanted side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
(53 reference statements)
4
30
1
Order By: Relevance
“…The following drugs were used in the present study: rac -CE-123 = 5-((benzhydrylsulfinyl)methyl)-thiazole (Kristofova et al, 2018) and S -CE-123 = S-5-((benzhydrylsulfinyl)methyl)thiazole (Nikiforuk et al, 2017). The dosage of the drugs and the time point of administration were selected according to previous studies in which it was shown that 10 mg of the drugs per kg body weight administered 30 min before testing produces significant learning and memory effects without causing detectable undesired side effects in rats (Nikiforuk et al, 2017; Kristofova et al, 2018). The drugs were dissolved in 1% DMSO and 3.3% Tween 80 diluted in 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following drugs were used in the present study: rac -CE-123 = 5-((benzhydrylsulfinyl)methyl)-thiazole (Kristofova et al, 2018) and S -CE-123 = S-5-((benzhydrylsulfinyl)methyl)thiazole (Nikiforuk et al, 2017). The dosage of the drugs and the time point of administration were selected according to previous studies in which it was shown that 10 mg of the drugs per kg body weight administered 30 min before testing produces significant learning and memory effects without causing detectable undesired side effects in rats (Nikiforuk et al, 2017; Kristofova et al, 2018). The drugs were dissolved in 1% DMSO and 3.3% Tween 80 diluted in 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Modafinil is a wake-promoting drug which is used to treat sleep apnea, narcolepsy and shift work sleep disorders (Battleday and Brem, 2015; Kristofova et al, 2018). Recently, the synthesis and test in different behavioral paradigms of modafinil analogue 5-((benzhydrylsulfinyl)methyl)-thiazole (CE-123; Kalaba et al, 2017; Nikiforuk et al, 2017) was reported. CE-123 was structurally modified by substituting the carboxyl-amide moiety of modafinil with a heterocycle thiazole group attached to position five which may provide a high metabolic stability of CE-123.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(S)-CE-123 ((S)-5-((benzhydrylsulfinyl)methyl)thiazole) was synthesized from the Lubec laboratory (University of Vienna, Austria) as reported previously [23]. In short, diphenylmethanol and thiourea were reacted to yield [(diphenylmethyl)sulfanyl]methanimideamide hydrobromide.…”
Section: Drugs and Treatmentsmentioning
confidence: 99%
“…A recently synthesized and chromatographically separated analog of modafinil, ( S ) -CE-123 ( Figure 1 ), is a highly selective atypical inhibitor of DAT that has been shown to enhance cognitive flexibility and reduce impulsivity in rats (Nikiforuk et al, 2017). The present paper describes the enantioselective synthesis and initial characterization of ( S ) -CE-123.…”
Section: Introductionmentioning
confidence: 99%